2020
DOI: 10.1177/1050651920910226
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Information in Social How-To Questions That Initiate Documentation

Abstract: This study introduces social question-and-answer (SQA) documentation to technical and professional communication scholarship. It conceptualizes SQA as interactive, user-generated documentation and describes contextual information types within social how-to questions that initiate documentation. It also explores whether contextual information associates with answers that complete the interactive documentation. Results reliably describe 15 information types based on content analysis of 3,529 contextual informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 55 publications
(134 reference statements)
0
6
0
Order By: Relevance
“…Askers in social Q&A can describe their problems with various cues. Question cues include informational cues (e.g., complexity), contextual cues (e.g., task specifications), emotional cues (e.g., sentiment, users' experiences), and social cues (e.g., socioemotional statements, politeness) (Baker, 2020; Calefato et al, 2015; Chua & Banerjee, 2015b; Deng et al, 2019; Hertzum & Borlund, 2017; Ostermaier‐Grabow & Linek, 2019; Ruthven et al, 2018; Sin et al, 2018). By adopting the GFT framework, we divide question cues into three dimensions: gain, hedonic, and normative goal‐frames.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Askers in social Q&A can describe their problems with various cues. Question cues include informational cues (e.g., complexity), contextual cues (e.g., task specifications), emotional cues (e.g., sentiment, users' experiences), and social cues (e.g., socioemotional statements, politeness) (Baker, 2020; Calefato et al, 2015; Chua & Banerjee, 2015b; Deng et al, 2019; Hertzum & Borlund, 2017; Ostermaier‐Grabow & Linek, 2019; Ruthven et al, 2018; Sin et al, 2018). By adopting the GFT framework, we divide question cues into three dimensions: gain, hedonic, and normative goal‐frames.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
“…Secondly, self-disclosure refers to the revealing of personal information in questions (Choi et al, 2013). Many askers describe personal information, situations, and experiences in questions (Baker, 2020;Hertzum & Borlund, 2017;Ruthven et al, 2018). The disclosure of personal cues tends to receive feedback with similar self-disclosure (Raban, 2009).…”
Section: Question Cuesmentioning
confidence: 99%
“…To Zhang et al, 2017). Previous studies demonstrated that most CQA services are free, and some online Q&A services (e.g., Google Answers) closed due to their paid service (Baker, 2020;F. Lin & Huang, 2013;Shah et al, 2009).…”
Section: Question Cues Emphasizing Gain Goalsmentioning
confidence: 99%
“…CQA askers describe their problems with various cues such as informational cues (e.g., complexity), contextual cues (e.g., task specifications), emotional cues (e.g., sentiment, self-disclosure), and social cues (e.g., socioemotional statements, politeness) (Baker, 2020;Calefato et al, 2015;Deng et al, 2019;L. Wang, Liu, et al, 2022;Ostermaier-Grabow & Linek, 2019;Ruthven et al, 2018;Sin et al, 2018;Stokhof et al, 2022).…”
Section: Question Cuesmentioning
confidence: 99%
See 1 more Smart Citation